2022
DOI: 10.1007/s12035-022-03024-w
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Alleviates NLRP3 Inflammasome–Induced Allodynia/Hyperalgesia in Murine Cerebral Cortex Following Transient Ischemia: Focus on TRPA1/Glutamate and Akt/Dopamine/BDNF/Nrf2 Trajectories

Abstract: Global cerebral ischemia/reperfusion (I/R) provokes inflammation that augments neuropathic pain. Cilostazol (CLZ) has pleiotropic effects including neuroprotection in several ravaging central disorders; nonetheless, its potential role in transient central ischemic-induced allodynia and hyperalgesia has not been asserted before. Rats were allocated into 4 groups; sham, sham + CLZ, and 45 min-bilateral carotid occlusion followed by a 48 h-reperfusion period either with or without CLZ (50 mg/kg; p.o) post-treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…In an animal study, cilostazol deactivated the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome [ 74 ], which is associated with atherosclerosis and CVD [ 75 , 76 ]. This anti-inflammatory potential was mediated by the downregulation of p65 NF-κB and the enhancement of sirtuin-1, leading to the downregulation of NLRP3, an apoptosis-associated speck-like protein, active caspase-1, and interleukin-1β [ 74 ].…”
Section: Beneficial Role Of Cilostazol In the Development Of Atherosc...mentioning
confidence: 99%
See 2 more Smart Citations
“…In an animal study, cilostazol deactivated the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome [ 74 ], which is associated with atherosclerosis and CVD [ 75 , 76 ]. This anti-inflammatory potential was mediated by the downregulation of p65 NF-κB and the enhancement of sirtuin-1, leading to the downregulation of NLRP3, an apoptosis-associated speck-like protein, active caspase-1, and interleukin-1β [ 74 ].…”
Section: Beneficial Role Of Cilostazol In the Development Of Atherosc...mentioning
confidence: 99%
“…In an animal study, cilostazol deactivated the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome [ 74 ], which is associated with atherosclerosis and CVD [ 75 , 76 ]. This anti-inflammatory potential was mediated by the downregulation of p65 NF-κB and the enhancement of sirtuin-1, leading to the downregulation of NLRP3, an apoptosis-associated speck-like protein, active caspase-1, and interleukin-1β [ 74 ]. In an animal study of hypercholesterolemic rats, cilostazol treatment protected against hypercholesterolemia-induced cardiac damage via molecular mechanisms targeting the crosstalk between Nrf2 induction and NF-κB inhibition in the heart [ 77 ].…”
Section: Beneficial Role Of Cilostazol In the Development Of Atherosc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past several decades, multiple studies have reported the role of Nrf2 in the mitigation of neuronal excitotoxicity. 33 , 34 , 35 , 36 Nevertheless, excitotoxicity owing to acute neurovascular insult typically results in irreversible necrotic cell death within minutes, which is hardly preventable or rescuable. Although Nrf2 has been studied extensively, the mechanism(s) of its neuroprotective effects is not fully understood and requires further research.…”
Section: Cell‐specific Role Of Nrf2 In the Acute Phasementioning
confidence: 99%
“…Excitotoxicity is a common way of neuronal death not only seen in acute brain ischemia but also present in other diseases such as chronic ischemia, trauma, and neurodegenerative disorders. Over the past several decades, multiple studies have reported the role of Nrf2 in the mitigation of neuronal excitotoxicity 33–36 . Nevertheless, excitotoxicity owing to acute neurovascular insult typically results in irreversible necrotic cell death within minutes, which is hardly preventable or rescuable.…”
Section: Cell‐specific Role Of Nrf2 In the Acute Phasementioning
confidence: 99%